Magnetic resonance imaging of the rotator cuff muscles after baseball pitching - Yanagisawa, O.; Niitsu, M.; Takahashi, H.; Itai, Y. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purposes of present study were to investigate quantitatively using functional MR imaging the effect of a series of throwing activities on rotator cuff muscles and to compare the effect of pitching with that of all-out shoulder external rotator exercise as the targeted external rotator muscle group (the infraspinatus and the teres minor). Methods: Experimental design: MRI measurements after 135 baseball pitches or all-out shoulder external rotator exercise (concentric mode) in each subject's nondominant shoulder. Participants: 6 amateur baseball pitchers. Measures: serial T2-weighted images of rotator cuff muscles were obtained before pitching (or shoulder exercise) and immediately, 30, 60 min, 24, 48, 96 hrs after pitching (or shoulder exercise). T2 relaxation times (T2) at each measurement time were calculated for the rotator cuff muscles. Results: Both the supraspinatus and the external rotator muscle group showed significant T2 elevations until 96 hrs after pitching. The subscapularis also showed significantly increased T2 until postpitching 48 hrs. On the other hand, a significant T2 elevation continued until 60 min after shoulder exercise, but thereafter returned towards the value at rest over the next 24 hrs. Conclusion: Long lasting T2 elevations in rotator cuff muscles would be associated with an increase in each intramuscular water content, and may be attributed to the muscle damage that resulted from eccentric contraction during pitching. This information should serve as a useful complement to shoulder injury prevention for baseball pitchers.